Motivations of collaborative obtainers and providers in Europe. Issue 5 (4th April 2022) - Torrent-Sellens, Joan; Cugueró-Escofet, Natàlia; Ertz, Myriam
ABSTRACT: The article analyses the motivations for participating in collaborative digital platforms in Europe. From the duality of roles approach, the motivations of European obtainers and providers are studied, with special emphasis on the role played by occupational status. For that purpose, a pan-European sample of 14, 050 citizens from 28 countries is investigated and a quantitative data analysis is applied through a system of structural equations. Regarding overall motivations, the research has identified that economic and usefulness motivations predict the obtaining of goods and services through collaborative platforms. In the case of provision, utility motivations are complemented by other pro-social predictors, such as the possibility of non-monetary exchanges. In addition, the occupational status of the individuals significantly determines their key motivations. Self-employed individuals are essentially motivated by price and novelty in explaining when they consider becoming obtainers. In contrast, managers are more motivated by convenience. In addition, self-employed individuals will be more likely to provide resources on collaborative platforms for non-monetary exchange reasons. Managerial implications of these results are also discussed.